Implementasi Model Project Based Learning dalam Mengembangkan Poster Materi Ajar Bahasa Indonesia pada Mahasiswa - Saputra, Ady; Bua, Mety Toding; Agustina, Mega (Lembaga Yasin AlSys, 2025)
The implementation of the Project Based Learning model aims to determine students' abilities in producing teaching materials. Teaching materials developed by students in the form of Indonesian language teaching materials are made in the form of poster. The implementation of the project-based learning model was carried out for students majoring in Elementary School Teacher Education, Faculty of Teacher Training and Education, University of Borneo Tarakan in the form of a One-Shot Case Study experimental research. The number of student samples was 43 people who took the Elementary School Indonesian Language Education course. The research data was obtained from the analysis of product observation sheets with a product feasibility scale. Data analysis with percentage technique and processed descriptively. The results of this research show that the Indonesian language teaching material posters developed by students are very suitable for use with a score of 95. It can be concluded that the Project Based Learning learning model can improve learning outcomes by developing Indonesian language teaching material posters for students.